International migration and development: perspective from origin countries of migrants - Kunwar, Laxman Singh (Economic Journal of Development Issues, 2015)
This paper seeks to critically analyze the role of migration to carry out development in origin countries of migrants. Now, migration and development; development in the origin of migrants’ is being widely discussed among governmental and non-governmental institutions in the world. At the same time the flow of migrants’ from economically less developed nations or regions to more developed nations or regions have been increased significantly. The volume of remittances also has been increased every year. Some countries adopted the policy of labour export since a long period of time but there is no achievement in development in the countries. The aim of this paper is to relate achievement in development of migrants’ origin countries with remittances with the help of available literature. The existing debate on migration and development is also a part of review of this paper. The migration-development relationship is complex and multidimensional, and that there is variation from one context to another with differences in the nature of migration and in the economic, political and social situations in origin and destination. It would be problematic and insufficient to analyze migration process and its consequences with the help of any single theory or approach of migration, because migration process has far reaching effects on national and international level and varies differently for different part of world on the basis of achievement on social, political, and economic development.  DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11865Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 60-75